Optimizing Company Value Through Digitalization, Tax Planning, and Capital Structure: Analysis of Its Influence on the Banking Sector in Indonesia - Handayani, Rizma Fitri; Misran, Alfian; Murti, Galuh Tresna (Adpebi International Journal of Multidisciplinary Sciences, 2025)
This study aims to test and analyze the influence of independent variables, namely Digitalization, Tax Planning, and Capital Structure on the dependent variable, namely Company Value using the Tobins'Q ratio to measure company value. The population of this study includes companies from the banking sector listed on the Indonesia Stock Exchange (IDX) in the 2020-2024 period. The research sample was selected using a purposive sampling technique, resulting in a total of 30 companies. Data analysis was carried out using multiple linear regression analysis with the help of the IBM SPSS Statistics application. The results of this study indicate that digitalization has a significant negative effect on company value, tax planning has a significant negative effect on company value, and capital structure has a significant positive effect on company value.